Recent contributions to the distribution of the freshwater ichthyofauna in Greece - KOUTSIKOS, N.; ZOGARIS, S.; VARDAKAS, L.; TACHOS, V.; KALOGIANNI, E.; SANDA, R.; CHATZINIKOLAOU, Y.; GIAKOUMI, S.; ECONOMIDIS, P.S.; ECONOMOU, A.N. (Mediterranean Marine Science, 2012)
In this paper we supplement Greece’s recent annotated inventory of freshwater fishes per hydrographic basin with recent distributional data and taxa alteration information, based on field sampling and a literature review up to September 2011. We report on newly documented distributional records of 31 fish species plus one unidentified taxon, within 35 hydrographic river basin units in Greece. These new records include 14 native fish species, seven alien and 12 translocated. Translocated taxa are distinguished from aliens, in order to report species non-indigenous to a basin but native within the same ecoregion. Twelve hydrographic basin units are newly added to the roster of ichthyologically explored river basins following a previous basin-scale inventory method (the total is now 117). This review increases the number of Greece’s freshwater fish taxa to 167, since four new species are added to the list (Carassius langsdorfii, Neogobius fluviatilis, Telestes alfiensis, Millerigobius macrocephalus) and two are deleted (Salmo dentex, Barbus rebeli) due to taxonomic changes. Taxonomic changes will probably continue to alter the national list since phylogenetic research is ongoing on several taxa in many parts of the country